Recovery kinetics of micronucleus formation by fractionated X-ray irradiation in various types of human cells. (29th June 2018) - Koyama, Shin; Narita, Eijiro; Shinohara, Naoki; Miyakoshi, Junji
Abstract: High-dose ionizing radiation is sufficient for breaking DNA strands, leading to cell death and mutations. By contrast, the effects of fractionated ionizing radiation on human-derived cells remain unclear. To better understand the genotoxic effects of fractionated ionizing radiation, as well as the cellular recovery rate, we investigated the frequency of micronucleus (MN) formation in various types of human cells. We irradiated cells with fractionated X-ray doses of 2 Gy at a rate of 0.0635 Gy/min, separated into two to eight smaller doses. After irradiation, we investigated the frequency of MN formation. In addition, we investigated the rate of decrease in MN frequency after irradiation with 1 or 2 Gy X-rays at various recovery periods. Fractionated irradiation decreased MN frequency in a dose-dependent manner. When the total dose of X-rays was the same, the MN frequencies were lower after fractionated X-ray irradiation than acute irradiation in every cell type examined. The rate of MN decrease was faster in KMST-6 cells, which were derived from a human embryo, than in the other cells. The rate of MN decrease was higher in cells exposed to fractionated X-rays than in those exposed to acute irradiation. Recovery rates were very similar among cell lines, except in KMST-6 cells, which recovered more rapidly than other cell types.